Investigation of the optical absorption dose response of LiF:Mg, Ti (TLD-100) and the role of V centers in F center (5.08 eV) bleaching. (July 2016) - Druzhyna, S.; Eliyahu, I.; Oster, L.; Horowitz, Y.S.; Biderman, S.; Reshes, G.; Orion, I.
Abstract: The optical absorption (OA) dose response of irradiated LiF:Mg, Ti has been measured over the dose range from 100 Gy to 1.4 M Gy. Measurements at high dose indicate that the 4.0 eV band is actually a composite band at 3.84 eV and 4.3 eV. Bleaching experiments at 5.08 eV (F band) support the participation of V3 centers in the relaxation mechanisms following the bleach. The results are interpreted in the framework of a spatially correlated trapping center/luminescent center giving rise to composite peak 5 in the glow curve. Highlights: New interpretation of the optical absorption spectrum. Extended dose response. V3 /Vk center participation.